Diseño y aplicación de un instrumento de evaluación formativa basado en aprendizaje significativo en una IED del municipio de La Mesa, Cundinamarca (2017)
The learning- teaching process is conformed by multiple components, but the most sensitive of all is the evaluation undeniably, maximum when it's incorporated like a part of learning process and not only with an outcome measure. Accordingly, evaluation should be a teachers' concern as the investigators group, authors of this study. For this reason, we began the very unpleasant task to draw attention over own job inside Educative Institution where we work. It is an official school in a neighboring municipality to capital of our country where is chosen meaningful learning as the pedagogical model to follow according to The Institutional Educational Project (PEI) however, in practice, this becomes some doubts that leading to the present research work. We start the first cycle with the question: What are evaluation's strategies implemented in the basic subjects in 702 Grade correspond with formative evaluation according to the Meaningful Learning Approach adopted by The Institution?...